Behavior of masonry infilled Chuandou timber frames subjected to in-plane cyclic loading. (15th May 2020) - Qu, Zhe; Fu, Xiang; Kishiki, Shoichi; Cui, Yao
Highlights: Three typical failure modes of masonry-infilled timber frames were identified. The interaction between the timber frame and the masonry infill was investigated. The limitation of the existing code equations for masonry wall strength is shown. Abstract: The Chuandou timber frame is a traditional timber structural system widely used for nonengineered residential houses in southwestern China; this system is featured by beam-to-column joints with direct penetration tenons and free-standing column bases. As concluded by a previous study, the Chuandou timber frames with proper infills have exhibited better seismic performance than un-reinforced masonry structures in terms of collapse prevention, although the mortise-tenon connections, masonry infills, timber beams and columns may have sustained various extents of damage. To investigate the seismic behavior of the structural system, six full-scale Chuandou timber frame subassemblies were subjected to in-plane quasi-static loading, four of which were infilled with masonry walls. The test results show that the masonry infills provided the most lateral resistance of the system, whereas the timber frames could sustain a large lateral drift without losing their vertical stability. The observed failure modes were identified from different specimens. The lateral strengths of the specimens in the current test were evaluated using the existing code equations. The results suggest the necessity of considering the aspect ratio in calculating the shear strength of masonry walls.